Optimalisasi Kelompok Tani Garam untuk Pemberdayaan Ekonomi Berbasis Sumber Daya Lokal di Pantai Selatan NTB - Fajar Nugraha; Lestari Yuliana; Ridwan Hakim (Lembaga Publikasi Ilmiah Nusantara, 2026)
This community service program aimed to optimize salt farmer groups to strengthen local resource based economic empowerment in the southern coastal area of West Nusa Tenggara. The program focused on improving institutional capacity, production practices, and product diversification among small scale salt farmers. The intervention was implemented through participatory training, technical assistance, and group based mentoring. Data were collected using observation, structured interviews, and documentation of production and income records before and after the program. The results showed measurable improvements in group management, production efficiency, and product value. Salt production quality increased through better handling and processing practices. Farmers began producing diversified salt products with higher market value. Group based management improved access to local markets and strengthened collective bargaining power. Economic outcomes showed an increase in average household income and more stable production cycles. These findings indicate that optimizing farmer groups through locally appropriate approaches can enhance economic resilience in coastal communities. The program provides a replicable model for community based economic empowerment that relies on local resources and collective action.